Eileen Leier : sur la piste de la ruée vers l’or - Campeau, Sylvain (CV Photo)

(untitled) (Les Productions Ciel variable, 1998)
Summary Eileen Leier's Sur la piste de la ruée vers l'or (On the gold-rush route) is a evidentiary installation that deals with the presence of remains and of photography in various ways. By coupling artifacts, materials, and objects that have been handled, archival images from the period, and contemporary images of the sites that are now deserted, Leier sketches out a series of equivalences and modes of reference between these various presences. It is a little as if, from one piece to another, a likelihood of the trace was always in play, transferred back and forth between the artifacts presented. Translation Käthe Roth